The Definitive Guide to the ARM Cortex-M3. - Yiu, Joseph (Elsevier, 2007)
This user's guide does far more than simply outline the ARM Cortex-M3 CPU features; it explains step-by-step how to program and implement the processor in real-world designs. It teaches readers how to utilize the complete and thumb instruction sets in order to obtain the best functionality, efficiency, and reuseability. The author, an ARM engineer who helped develop the core, provides many examples and diagrams that aid understanding. Quick reference appendices make locating specific details a snap!. Whole chapters are dedicated to:. Debugging using the new CoreSight technology. Migrating effe.